GE_GERICHTE P/25835/2019 vom 10. Dezember 2020 - GE Cour de justice (2020)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;PRESCRIPTION;APPROPRIATION ILLÉGITIME;VIOLATION DE DOMICILE;SUBSTITUTION DE MOTIFS | CPP.310; CP.31; CP.137